2013
DOI: 10.1186/1472-6874-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Improved quality of life after surgery for pelvic organ prolapse in Nepalese women

Abstract: BackgroundPelvic organ prolapse (POP) is a common gynecological condition that can affect quality of life (QOL) in women. In Nepal, the prevalence of POP is high, but many affected women are still deprived of treatment. Vaginal hysterectomy with pelvic floor repair is one of the common treatment options for advanced POP. However, QOL outcomes after surgery have not been reported in low-income countries. Thus, we aimed to examine changes in QOL among Nepalese women with POP after such surgery.MethodsThis longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
25
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 20 publications
15
25
1
4
Order By: Relevance
“…Studies suggest that literacy plays an important role for women to have health related knowledge and better reproductive health outcomes, as they are able to have easier access to information. 11,12 The reason for younger women to have more knowledge could be because of the better access to education in recent years and more family planning programs targeting young mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that literacy plays an important role for women to have health related knowledge and better reproductive health outcomes, as they are able to have easier access to information. 11,12 The reason for younger women to have more knowledge could be because of the better access to education in recent years and more family planning programs targeting young mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to perform research on depressive symptoms and QOL in women before and after prolapse surgery. 3,4…”
Section: Phq-9 Is a Validated Measurement Of The Severity Of Depressimentioning
confidence: 99%
“…Ghetti C reported that women with pelvic organ prolapse had a higher prevalence of depressive symptoms compared to controls without prolapse. [2][3][4] Examination of depression and quality of life using a self-administered questionnaire consists of the Patient Health Questionnaire (PHQ-9), Pelvic Floor Distress Inventory (PFDI), and Pelvic Floor Impact Questionnaire (PFIQ).…”
mentioning
confidence: 99%
“…The prevalence of POP at the global level is 2 to 20% in women under the age of 45 years. 1 Many factors contribute to POP, especially those related to childbirth, such as multiparity, instrumental delivery, prolonged labor, and giving birth to a macrosomic infant. 2 In general, treatment of POP varies depending on the extent of the pelvic organ descent, the reported symptoms, woman's general health, and the surgeon's preference and competences.…”
Section: Introductionmentioning
confidence: 99%